Aktivitas Antijamur Ekstrak Etanol Daun Matoa (Pometia Pinnata J.R. & G.Forst) Terhadap Pertumbuhan Jamur Trichophyton Mentagrophytes - Wahyu Margi Sidoretno; Mirna Gustari (Sistem Informasi, 2021)
The matoa plant is widely used to treat infectious diseases caused by bacteria and fungi. The purpose of this study was to determine the antifungal activity of the ethanolic extract of matoa (Pometia pinnata) leaves on the growth of Trichophyton mentagrophytes at various concentrations 10%, 20%, and 30%. Trichophyton mentagrophytes are a type of fungus that belongs to the dermatophyte group that causes dermatophytoses (ringworm). The experimental laboratory methods were used in this study. The antifungal activity was determined by using the agar diffusion method. Ketoconazole was used as the positive control, and DMSO was used as the negative control. This study showed the inhibition zone of the extract with concentrations 10%, 20%, 30% were 23.05 mm, 24.86 mm, 25.05 mm, respectively. Ketoconazole as positive control showed the inhibition zone 28.56 mm. From the results, it can be concluded that the ethanolic extract of the leaves of matoa (Pometia pinnata) has potential antifungal activity against Trichophyton mentagrophytes.